2019
DOI: 10.1016/j.celrep.2019.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Differences in the Vegf/Vegfr Code Reveal Organotypic Roles for the Endothelial Cell Receptor Kdr in Developmental Lymphangiogenesis

Abstract: Highlights d Kdr is important for lymphatic vascular development d Vegf/Vegfr regulation of lymphatic development is spatially dependent d The Vegf/Vegfr binding code in zebrafish has shifted compared with mice and humans d Lymphatic fate throughout the zebrafish embryo is driven by Vegfr signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
(120 reference statements)
1
21
0
Order By: Relevance
“…The homeobox transcription factor Prox1 plays pivotal roles in the development of embryonic lymphatics and in the maintenance of the adult lymphatic system by regulating various LEC related factors, such as VEGFR-3 ( Yang and Oliver, 2014 ). Kdr (a VEGFR-2 homolog) is indispensable for craniofacial lymphangiogenesis in zebrafish and is involved in the proliferation and migration of LECs ( Vogrin et al, 2019 ). c-Jun participates in the proliferation of LECs ( Wissmann and Detmar, 2006 ), while Ets1, an important transcription factor of the Ets family, is required for Kaposi’s sarcoma-associated herpesvirus (KSHV)-induced expression of VEGFR-3 and lymphangiogenesis ( Gutierrez et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homeobox transcription factor Prox1 plays pivotal roles in the development of embryonic lymphatics and in the maintenance of the adult lymphatic system by regulating various LEC related factors, such as VEGFR-3 ( Yang and Oliver, 2014 ). Kdr (a VEGFR-2 homolog) is indispensable for craniofacial lymphangiogenesis in zebrafish and is involved in the proliferation and migration of LECs ( Vogrin et al, 2019 ). c-Jun participates in the proliferation of LECs ( Wissmann and Detmar, 2006 ), while Ets1, an important transcription factor of the Ets family, is required for Kaposi’s sarcoma-associated herpesvirus (KSHV)-induced expression of VEGFR-3 and lymphangiogenesis ( Gutierrez et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…To validate the findings obtained from the microarray (Table 1), we first analyzed the mRNA levels of Kdr, c-Jun (cluster 13), Stc1 (cluster 8), Sparc (cluster 7), and Ets1 (cluster 0), which have been reported to be associated with LECs migration and proliferation or lymphangiogenesis (Wissmann and Detmar, 2006;Gutierrez et al, 2013;Vogrin et al, 2019). The qPCR results revealed that Ang II treatment upregulated the mRNA levels of Kdr, c-Jun and Stc1 but reduced the mRNA levels of Sparc and Ets1 in LECs in a time-dependent manner compared with control ( Figure 7A).…”
Section: Validation Of Gene Expression In Ang Ii-treated Lecs By Qpcrmentioning
confidence: 99%
“…The formation of the craniofacial lymphatic vasculature occurs in a very different manner to lymphatics in other tissues and provides compelling evidence for heterogeneity in developmental and cellular processes ( Okuda et al, 2012 ; Astin et al, 2014 ; Shin et al, 2016b , 2019 ; Eng et al, 2019 ; Vogrin et al, 2019 ). For example, Eng and colleagues lineage traced cells that contribute to facial lymphatics using the photoconvertible Kaede protein.…”
Section: Heterogeneity In Cellular Mechanisms In Zebrafish Vascular Dmentioning
confidence: 99%
“…However, even murine VEGF-D reportedly differs from human VEGF-D in its inability to interact with mouse VEGFR-2 [68]. Exactly the opposite seems to be the case in zebrafish, where the VEGF-D-VEGFR-3 interaction was reported to be absent [69], implying that lymphangiogenesis might happen in zebrafish independently of VEGFR-3. While direct demonstrations of the substrate specificities of the zebrafish Adamts proteases are still missing, it appears clear that zebrafish data are not easily extrapolated to mammals.…”
Section: Species-specific Differencesmentioning
confidence: 98%